DESCRIPTION OF FAMILY SUPPORT FOR CHRONIC KIDNEY FAILURE PATIENTS AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Julia Ringgas Fransiska Siregar; Tampubolon, Lindawati Farida; Sembiring, Friska (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Chronic Kidney Failure (CKF) is a common health issue found in every community and has become a global concern, including in Indonesia. One aspect of this issue is the increasing number of cases requiring therapy 2-3 times a week. Family support can positively impact the survival of patients, with families accepting their members in any condition. The aim of this study is to understand the overview of family support for chronic kidney failure patients at Haji Adam Malik General Hospital, Medan, in 2023. This research uses a descriptive design with a population of 403 individuals. The instrument used is a family support questionnaire. The sampling technique used is purposive sampling, totaling 67 samples. The results showed that family support for chronic kidney failure patients undergoing hemodialysis at Haji Adam Malik General Hospital, Medan, is considered good by 57 respondents (85.1%). The majority of respondents are male, with 43 respondents (64.2%), and the average duration of hemodialysis is 45.47 months. Most respondents have a high school education, with 27 respondents (40.3%), and the majority are married, with 52 respondents (77.6%). The conclusion of this study is that the overview of family support for chronic kidney failure patients undergoing hemodialysis at Haji Adam Malik General Hospital, Medan, is considered good by 57 respondents (85.1%). It is recommended that family visits to patients undergoing hemodialysis therapy be conducted regularly.